Peningkatan Pengetahuan dan Perilaku dari Pola Diet dan Senam Kaki Diabates pada Pasien Diabetes Mellitus di Keluarga Binaan Puskesmas Depok Utara - Febiya Ningrum , Indriyani; Kristanti, Melly; Nabila, Adelia; Dini, Theresia; Safira, Ramadhani; NurCita, Boenga; Redha, Pratiwi Soni (Jurnal Abdimas Kesehatan (JAK), 2025)
Diabetes mellitus is the 9th indicator in the SPM (Minimum Service Standard) in the health sector. The district/city government is obliged to provide health services according to standards to all DM patients aged 15 years and above as a secondary prevention effort in their work area for a period of one year. This activity will be held in January 2024 in Beji Village, Depok City. This activity is in the form of an intervention, namely counseling using leaflets for 15 minutes by approaching the community door to door regarding diet and diet as well as diabetic foot exercises. The subjects of this activity are families and patients who have diabetes mellitus. Based on the results, it was obtained that the increase in knowledge and behavior of families and patients with diabetes mellitus was evidenced by a p-value of 0.004 pre-test (73 (66-74); post-test 5.67 (79-91)); P-value knowledge 0.003 pre-test (63.67(56-74); post-test 76 (67-87)). Therefore, it is necessary to provide diabetic foot exercises from the health center and counseling about the dangers of diabetes to patients and patients' families, to be able to prevent complications to patients and prevent increased risk of diabetes from the patient's family.